Baby care and parentality building: the father in focus (Research, Society and Development, 2020)
This article aims to discuss the parental relationship in early childhood and the importance of early care with the baby, focusing on the experience of parenting. The method used for this study was the narrative literature review technique. A survey was conducted in the national literature on the chosen theme. It can be said that the birth of a child is accompanied by different fantasies, regardless of whether this child was planned or not, because parents need to learn to deal with this new moment of their lives. It can be seen that in our culture the mother figure is seen most prominently in the initial relations with the baby and the father occupies a secondary place. However, current studies prove the importance of the presence of the father and paternal care for the development of the child in early childhood and address the issue of paternal authority, from a point of view that provides an affective bond, which is permeated by respect and trust between father and son. For the construction of parenting it is important to reflect on the responsibility of the father, considering that today it is recognized that the baby has an active role in family affective relationships.